The Implementation of Learning English for Aviation for Improving the Students’ English Skills - Fauzan, Surya; Amin, Fatimah Hidayahni; Sakkir, Geminastiti (Journal of Excellence in English Language Education, 2025)
This study aims to see the learning model applied by lecturers in improving students' English skills and to see the lecturer and students' views on the English for Aviation course. This research uses a qualitative method with a case study design, where data is collected through observations checklist and conducting interviews with purposive sampling. Data were analysed by data reduction, data display, conclusion drawing and verification. The use of an integrated learning model is considered to take an important role by lecturers considering the short duration of learning, where several aspects of English Skills are combined into one learning material. In addition, speaking and listening are the two aspects that lecturers pay attention to considering that aviation learning is more communication with passengers. Students' views on the application of English for Aviation have had a positive impact on improving listening and speaking skills. However, students feel that certain aspects, such as the lack of variety in instructional methods and the limited class duration, hinder the achievement of optimal learning outcomes.